Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1365-8711.2003.06204.x
|View full text |Cite
|
Sign up to set email alerts
|

Parsec-scale Faraday rotation distribution in the BL Lac object 1803+784

Abstract: We present the results of VLBI polarization observations of the BL Lac object 1803+784 made simultaneously at 22, 15, 8 and 5 GHz in 1997 April, and quasi-simultaneously at 1.6 and 5 GHz in 1998 July. These data have yielded the total intensity, polarization, spectral-index, and rotation-measure distributions on scales from less than 1 mas to about 30 mas from the core (from a projected distance of about 1-150 pc at the redshift of 1803+784). There is an enhancement in the rotation measure for the VLBI core, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
3
33
1
Order By: Relevance
“…There is a clear systematic gradient in the RM across the VLBI jet, extending from the core region to a distance of about 30 mas from the core. This confirms the previous detection of such a RM gradient based on observations at 5, 8 and 15 GHz (Gabuzda et al 2004) and provides new support for the hypothesis that a helical magnetic field is associated with the jet of Mrk 501.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There is a clear systematic gradient in the RM across the VLBI jet, extending from the core region to a distance of about 30 mas from the core. This confirms the previous detection of such a RM gradient based on observations at 5, 8 and 15 GHz (Gabuzda et al 2004) and provides new support for the hypothesis that a helical magnetic field is associated with the jet of Mrk 501.…”
Section: Discussionsupporting
confidence: 90%
“…This is among the first VLBI polarization studies of AGN at frequencies as low as 1.6 and 2.2 GHz (e.g. Gabuzda & Chernetskii 2003; Pushkarev et al 2005; Hallahan & Gabuzda 2008).…”
Section: Observations and Calibrationmentioning
confidence: 84%
“…Moreover, while VLBI studies of quasars have revealed non‐uniform rotation measure distribution on the parsec scale (Taylor 1998, 2000; Nan et al 1999), the situation is not clear in BL Lac objects. OJ 287 shows no substantial rotation measure intrinsic to the BL Lac object (Gabuzda & Gómez 2001), while intrinsic rotation measure is found in the core of BL Lac itself (Reynolds, Cawthorne & Gabuzda 2001), and 1803+784 (Gabuzda & Chernetskii 2003).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed and studied with different VLBI arrays at a range of different frequencies (e.g., Eckart et al 1986Eckart et al , 1987Witzel et al 1988;Charlot 1990;Strom & Biermann 1991;Fey et al 1996;Gabuzda 1999;Gabuzda & Cawthorne 2000;Gabuzda & Chernetskii 2003;Ros et al 2000Ros et al , 2001Britzen et al 2005aBritzen et al ,b, 2008). …”
Section: Application To 1803+784mentioning
confidence: 99%